Clinical profile of patients with lupus nephritis - A.C. Schönrock (Reumatismo, 2011)
To the Editor Lupus nephritis is the strongest predictor of systemic lupus erythematosus (SLE) patient’s morbidity and mortality with a prevalence varying from 31 to 65% according to the studied population (1). As the onset of lupus nephritis is usually silent, knowing possible association with others symptoms is useful in order to keep of better vigilance on patients with higher possibility to develop it. Pistiner et al described that lupus patients with nephritis also have an increased frequency of other severe lupus manifestations (2). According to Huong et al, in a study of 180 patients with lupus renal involvement, patients with nephritis suffered more commonly from malar rash, psychosis, myocarditis, pericarditis, lymphadenopathy and hypertension...